Matemática e educação ambiental no ensino fundamental: a construção de cisternas e as relações de proporcionalidade - Reis, Camila dos (2022)
Worldwide, but especially in Brazil, public environmental conservation and preservation policies are becoming increasingly urgent. With this in mind, it is understood that the school has a fundamental role in environmental education and awareness. In this sense, the present work aims to evaluate the contributions in the proportionality study teaching and learning process from a didactic proposal that involves environmental and mathematics education. In the study, students from the senior year of a municipal elementary school in Porto Alegre developed a project related to the use of water and the construction of cisterns models to study proportional quantities. Experimental research was carried out with two groups. In the first group (C31- Control Group), the study of proportional quantities was treated more traditionally through the exposure of subjects on the blackboard and textbook use. In the second group (C32 - Experimental Group), students carried out a survey with their community on water consumption; they studied cisterns and proportional quantities; they built their own cisterns models, discussing the magnitudes and proportions in the process; finally, they gave classes to younger students and built mini cisterns, as a permanent item for the school. The data for the research were analyzed quantitatively from the application of two exams in both classes, one at the beginning and the other at the end of the project. Correct resolutions, the identification of the type of proportion, and the method applied were scored. In the first evaluation, the predominant method used was the rule of three, while in the second evaluation, the results showed an increase of approximately six times the use of the proportional quantities properties by the experimental group. In the general context, the experimental group showed better performance in identifying, manipulating, and applying mathematical concepts. In a complementary way, qualitative research was carried out through a survey to determine which elements were the most motivating for each group and which class felt more motivated during the learning process. The answers allowed us to conclude that the experimental group had a more significant experience. They felt motivated to be part of a team and contribute to the school and the community.